Pengembangan bisnis jasa “kaluna badminton club” menggunakan business model canvas - Ashari, Bagus Lintang; Pahlevi, Reza Widhar (Academy of Education Journal, 2024)
Kaluna Badminton Club is a service business that provides a platform for young children to teenagers to become talented and accomplished athletes by practicing using the correct basic badminton techniques. The purpose of establishing this business is because there is not yet a single club that accommodates children from young age to adults to become proficient at playing badminton with the correct basic techniques in Imogiri District. This research was conducted to find out how to manage and develop business strategies at the Kaluna Badminton Club using the Business Model Canvas concept. The Business Model Canvas framework is used as a tool to achieve business targets in a detailed and structured manner. By using this study, it becomes easier for business processes to achieve their goals. The research results from this Business Model Canvas identification can provide the right business strategy choices for the Kaluna Badminton Club in each block. The blocks on the Business Model Canvas include customer segments, value propositions, channels, customer relationships, key resources, key activities, key partners, cost structure, revenue streams. Each of these blocks has its own role which is very important for achieving the business model.